Feeding ecology of fish larvae from Chilean Patagonia during austral winter - Landaeta, Mauricio F.; Vera-Duarte, Javier; Ochoa-Muñoz, María José; Bustos, Claudia A.; Balbontín, Fernando (Revista de Biología Marina y Oceanografía, 2019)
Feeding habits of the ichthyoplankton from Chilean Patagonia (44-46°30’S) were studied during June-July 2012 (austral winter). Ichthyoplankton assemblage was composed by 10 species, with low abundance (3.8 to 16.73 ind. 1000 m-3). Most abundant larvae were Maurolicus parvipinnis, Leptonotus blainvilleanus and Sprattus fuegensis. These three species fed mainly on calanoid copepodites, Paracalanus indicus and Calanus sp. copepodites, and cyphonautes. Trophic overlap among dominant fish larvae was high (Schoener’s D > 0.69) and no significant differences were detected in prey composition and size. Therefore, no resource partitioning occurred in planktonic fish larvae during winter 2012 in Chilean Patagonia.